Enhancing Information Sharing in Family Drug Courts: A Lean Six Sigma Case Study. (1st September 2017) - Kovach, Jamison V.; Curiel, Veronica; Franklin York, Alicia; Bogard, Sarah; Revere, Lee
Abstract: Given the variety of stakeholders involved in cases within family drug courts, efficient communication and information sharing, which are needed to support decision‐making, can be quite challenging. Through a case study in one family drug court system, this research employed an action research approach to improve the information sharing process following the Lean Six Sigma methodology. The solutions implemented through this study contributed to improving the quality of the services provided by this court system and its overall productivity. In addition, this research extends our knowledge about methods for improving court systems from which others can learn to guide future improvement efforts.